Gingival lipoma: a case report - Pablo Emilio Molano-Valencia; Vanessa Alejandra Betancourt-Rivera; Lina María Ruiz-Mazuera (Universidad de Antioquia, 2017)
The lipoma is a benign neoplasm of slow growth composed of mature fatty cells, usually surrounded by a thin fibrous capsule. It does not commonly appear in the oral cavity, corresponding to 0.1 to 5% of benign tumors of the mouth. This article presents the case of a 76-year-old female patient with a lesion on papilla and vestibular area between molars 46 and 47, measuring approximately 1.3 x 1.0 cm. The lesion was nucleated and subjected to histological examination, being compatible with a lipoma. This article describes its clinical features, differential diagnosis with other diseases of the oral cavity, and its respective management.